Преобразуйте выражение

f(x)=5sinx+12cosx5^2+12^2=25+144=169=13^2f(x)=5sinx+12cosx=[frac{cdot 13}{cdot 13}]=13cdot (frac{5}{13}sinx+frac{12}{13}cosx)(frac{5}{13})^2+(frac{12}{13})^2=frac{25+144}{169}=frac{169}{169}=1; ; Rightarrow ; ; frac{5}{13}=cos alpha ,; frac{12}{13}=sin alpha ; ,; tak; kaksin^2 alpha +cos^2 alpha =1tg alpha =frac{sin alpha }{cos alpha }=frac{12}{5}f(x)=13cdot (cos alpha cdot sinx+sin alpha cdot cosx)=13cdot sin(x+ alpha ),

где  tg alpha =frac{12}{5}alpha =arctgfrac{12}{5}.

Оцени ответ
Подпишись на наш канал в телеграм. Там мы даём ещё больше полезной информации для школьников!

Загрузить картинку
×